2022
DOI: 10.3389/fnut.2022.896427
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Association With Sarcopenia in Patients Undergoing Maintenance Hemodialysis Assessed by Nutritional Risk Index

Abstract: BackgroundMalnutrition and sarcopenia are frequently observed in patients undergoing maintenance hemodialysis (MHD). To elucidate whether malnutrition is associated with sarcopenia in those cases, the relationship of nutritional status with sarcopenia was investigated.MethodsNutritional status was assessed using a nutritional risk index (NRI) developed for patients undergoing MHD. This retrospective cross-sectional study included 315 MHD patients (199 males, 116 females), who were divided into low-risk (score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition to age-related processes, sarcopenia in potential KT recipients is also worsened by various factors, including malnutrition, metabolic acidosis, accumulation of uremic toxins, and amino acid loss during dialysis, as well as typical low-threshold inflammation [34]. Malnutrition is very common in patients requiring dialysis and leads to sarcopenia in these patients by reducing muscle mass and strength as well as physical performance [35]. Furthermore, dialysis patients have a lower physical activity compared to healthy people of the same age, which in turn increases muscle wasting [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age-related processes, sarcopenia in potential KT recipients is also worsened by various factors, including malnutrition, metabolic acidosis, accumulation of uremic toxins, and amino acid loss during dialysis, as well as typical low-threshold inflammation [34]. Malnutrition is very common in patients requiring dialysis and leads to sarcopenia in these patients by reducing muscle mass and strength as well as physical performance [35]. Furthermore, dialysis patients have a lower physical activity compared to healthy people of the same age, which in turn increases muscle wasting [36].…”
Section: Discussionmentioning
confidence: 99%
“…The new index included only four objective indicators, namely BMI, serum albumin, and total cholesterol and creatinine levels [ 51 ]. Subsequent studies have confirmed [ 24 , 52 ] that NRI-JH is a useful tool for assessing the nutritional status of dialysis patients and that its score is significantly associated with sarcopenia in dialysis patients.…”
Section: Related Index Of Malnutrition In Dialysis Patientsmentioning
confidence: 97%
“…Good nutrition has been shown to be protective against sarcopenia [39]. Hemodialysis patients often experience Protein-energy wasting (PEW), a state of disordered catabolism resulting from metabolic and nutritional derangements in chronic disease states [40].…”
Section: Malnutrition Assessmentmentioning
confidence: 99%